PENGARUH JUMLAH KREDIT YANG DIBERIKAN DAN NON PERFORMING LOAN (NPL) TERHADAP TINGKAT KEUNTUNGAN PADA KOPERASI UNIT DESA (KUD) DI KABUPATEN MALANG PERIODE 2013-2017 - Nurul Yuliati; jeni Susyanti; Muhammad Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACT This research has purpose to know the influence of number of credit given and Non Performing Loan (NPL) toward benefit rank to the Village Unit Cooperatives (KUD) in Malang Regency for the 2013-2017 period. This research is a kind of quantitative research which use multiple linear regression analysis. Taking sample of this research use purposive sampling technique which is technique of taking sample based on certain criteria and got six cooperatives from 31 cooperatives as population.The results show there is a significant effect between the amount of credit given to the level of profit. Non Performing Loans (NPL) have a significant effect on the level of profit. Based on the results of the research obtained, it is suggested to the cooperatives to maintain their credit quality and more selective in providing credit to their customers. And then to put more emphasis on the principle of vigilance in carry out lending activities. So that, the credit provided is not a lot of failure or problematic which can lead to increased NPL value. Keywords: Amount of Credit given, Non Performing Loan (NPL) and Rate of Profit.